Inovasi Atraksi Wisata Berbasis Video Virtual Tour Reality 3600 Sebagai Alternatif Menghadapi Era New Normal di Taman Gandrung Terakota Desa Tamansari Banyuwangi - Muhammad Ari Perdana; Ayu Wanda Febrian; Masetya Mukti; Junaedi Adi Prasetyo; Ella Nuritasari (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Gandrung Terakota Park is one of the objects that offer a fairly complete tourist attraction. This tourist attraction offers cool and beautiful natural beauty, combined with artificial attractions in the form of statues of Gandrung dancers numbering in the hundreds, as well as performing arts and entertainment. In efforts to maintain and improve its existence in the current new normal condition, Taman Gandrung Terakota requires innovation of attraction products. There needs to be a new adaptation of travel style as an alternative for tourists. One thing that can be done is through virtual video tours with virtual reality 3600 technology. This technology allows tourists to feel comfortable by watching videos about the exploration of the Gandrung Terakota Park guided by a Tour Guide. This video is designed as real as possible so that tourists can enjoy the surrounding scenery and can be played 3600. This form of innovation is very safe in current conditions and for all ages because it allows tourists to still enjoy the sensation of traveling without having to physically interact with the range of views that can be seen from the ground. Therefore, the existence of this community service program is considered important, which is carried out through the transfer of knowledge and technology transfer in the form of making a virtual reality 3600 video tour as an alternative to face the new normal era at Gandrung Terakota Park.